ANALYSIS OF VARIATIONS IN LOADING AND SPEED ON THE CONVERSION SPEED OF THE SUZUKI A100 ELECTRIC MOTORCYCLE USING BLDC - Rafi’i, Ahmad; Jerri, Jerri; Khalid, Muyassar; Perdana, Yuan; Nur, Raybian (JTAM ROTARY, 2025)
Penelitian ini bertujuan Untuk  mengetahui langkah Memodifikasi penggerak sepeda motor Suzuki A100 dari mesin Ke BLDC dan menganalisa variasi pembebanan dan speed terhadap kecepatan konversi motor listrik Suzuki A100 dengan penggunaan BLDC tipe Hub.Metode penelitian ini adalah penelitian kuantitatif yang dilakukan dengan melakukan eksperimen, dan kegiatan penelitian ini dilakukan dengan memodifikasi sepeda motor Suzuki A100 dari mesin ke BLDC Dan pengambilan data kecepatan yang dipengaruhi oleh beban dan speed yaitu beban 0 kg, beban 60 kg dan beban 120 kg, dengan Speed 1, 2 dan 3, Hasil penelitian menunjukan bahwa kecepatan pada beban 0 kg terhadap speed 1 sebesar (50 km / jam), speed 2 (61 km/jam), dan speed 3 sebesar (65 km/jam). Beban 60 kg terhadap speed 1 sebesar (47 km/jam), speed 2 (51km/ jam), dan speed 3 (52km/jam). Beban 120 kg terhadap speed 1 sebesar (44 km/jam), speed 2 (47km/jam), dan speed 3 (48 km/jam). This research aims to determine the steps to modify the Suzuki A100 motorbike drive from engine to BLDC and analyze variations in load and speed regarding the conversion speed of the Suzuki A100 electric motorbike using a Hub type BLDC. This research method is quantitative research carried out by conducting experiments and research activities. This was done by modifying the Suzuki A100 motorbike from engine to BLDC and taking speed data which was influenced by load and speed, namely 0 kg load, 60 kg load and 120 kg load, with Speed 1, 2 and 3. The results showed that the speed of the load 0 kg against speed 1 is (50 km/hour), speed 2 is (61 km/hour), and speed 3 is (65 km/hour). A load of 60 kg at speed 1 is (47 km/hour), speed 2 (51km/hour), and speed 3 (52km/hour). A load of 120 kg at speed 1 is (44 km/hour), speed 2 (47km/hour), and speed 3 (48 km/hour).